Paradoxical cold conditions during the medieval climate anomaly in the Western Arctic - Schimmelpfennig, I; ASTER Team; Mokadem, F; Leanni, L; Adamson, K; Verfaillie, D; Schimmelpfennig, D; Jomelli, V; Lane, TP; Favier, V; Masson-Delmotte, V; Swingedouw, D; et al. (Scientific Reports, 2016)
In the Northern Hemisphere, most mountain glaciers experienced their largest extent in the last millennium during the Little Ice Age (1450 to 1850 CE, LIA), a period marked by colder hemispheric temperatures than the Medieval Climate Anomaly (950 to 1250 CE, MCA), a period which coincided with glacier retreat. Here, we present a new moraine chronology based on 36Cl surface exposure dating from Lyngmarksbræen glacier, West Greenland. Consistent with other glaciers in the western Arctic, Lyngmarksbræen glacier experienced several advances during the last millennium, the first one at the end of the MCA, in ~1200 CE, was of similar amplitude to two other advances during the LIA. In the absence of any significant changes in accumulation records from South Greenland ice cores, we attribute this expansion to multi-decadal summer cooling likely driven by volcanic and/or solar forcing, and associated regional sea-ice feedbacks. Such regional multi-decadal cold conditions at the end of the MCA are neither resolved in temperature reconstructions from other parts of the Northern Hemisphere, nor captured in last millennium climate simulations.